A Process-Oriented Study of Translation Challenges and Competencies among Indonesian EFL Students - Sinaga, Inta Masni; Noryatin, Yeni (Universitas 17 Agustus 1945 Surabaya, 2025)
This study examined the challenges encountered by fourth-semester students in the English Department of STBA JIA during text translation in the Translation class. Additionally, the competency requirements of students for these tasks should be identified based on translation process translation challenges identified by many experts, and skills outlined by Dewi (2019). This research employs qualitative methodologies utilizing techniques for interviews with six students. The research findings lack knowledge and context and multiple meanings/ambiguity. In the next stage, transfer - conveying the meaning of source text into the target text, the challenges involve choosing the proper technique, method, strategy, or procedure and addressing cultural differences. In the subsequent restructuring phase, the challenge comes from the linguistic structure of the target text. The competency requirements of students must be considered, considering the challenges identified. The competencies needed to overcome those challenges are subject/ knowledge competence, terminological competence, transfer competence, cultural competence, and target language competence. While previous studies have discussed general difficulties faced by EFL students in translation, few have specifically examined how these challenges correspond to each phase of the translation process. The findings show that translation classes should not just focus on language accuracy, but also on increasing students' cultural awareness and subject-specific knowledge. Therefore, including domain-based vocabulary drills and providing Computer-Assisted Translation (CAT) tools into the curriculum is highly suggested.